Peningkatan Keterampilan Siswa Kelas XI Dalam Mata Pelajaran Prakarya Dan Kewirausahaan (PKWU) Melalui Model Pembelajaran Project Based Learning (PJBL) - Widya NP, Bq Ritasari; Zainurrahman, M (Alpatih Harapan Semesta, 2023)
This study aims to determine the improvement of students' skills in the PKWU subject of class XI through the PJBL learning model at SMA N 1 Suralaga. The method used in this study is Classroom Action Research (PTK), a qualitative approach. Data collection techniques used through observation, interviews, and documentation. Data analysis techniques use comparative techniques and qualitative data analysis. The results of the study showed that in cycle I of 38 students, the highest score was 85 for 15 students, while the lowest score was 40 for 23 students. While in cycle II all achieved a level of success above 75, where 8 students got a score of 100, while 30 students got a score of 85